Influence of Khat (Miraa) Production, Trade and Consumption On Primary School Dropout among the Boys in Kangeta Division, Igembe South District, Kenya - Njeru, Lucy K. (Egerton University, 2013)
Education for all is a global development need. Achievement of universal primary education is addressed by the second United Nations Millennium Development Goals (MDG). In a bid to achieve this goal, Kenya government initiated Free Primary Education (FPE) in January 2003. However, despite this effort, there has been educational wastage through declined enrolments and increased dropout rates, which are common phenomena in Kangeta Division, Igembe South District. The purpose of this study was to determine the influence of khat production, trade and consumption on primary school dropout among boys in the Division. The study focused on boys aged 6-16 years and was guided by 3 research questions. These were. does providing the required labour for khat production cause the primary school boys to drop out of school?; how does khat consumption by primary school boys influence boys’ school dropout?; to what extent does khat trade by primary school boys influence their school dropout?. The study adopted a cross-sectional survey design. A sample size of 210 dropouts was used based on Balians’ recommendation of having an average sample of 200 respondents adjusted by 10-15 % to cater for attrition. All the head teachers of the selected 10 schools were included in the sample to give a total of 220 respondents. Questionnaire and interview guide whose reliability coefficients were alpha 0.83 and 0.72 respectively were used for data collection. Validity of the instrument was ascertained by a panel of five experts from the department of Agricultural Education. Data was analyzed by a t-test and a chi-square test using the SPSS software package. Frequency tables and percentages summarized the results. The study findings indicated that the drop out of school among the primary school boys in the Division is as a result of providing cheap labour in miraa production. The findings revealed the effects of khat chewing to the behaviour of the user and it is this behaviour that causes the boys to drop out of school. The findings further indicated that the easy money these boys earn after engaging in khat business influence them to drop out of school. These findings of the study would be useful to the entire community, educationists and policy makers in finding ways of reducing the school dropout for the boys in Kangeta Division.
A Thesis Submitted to Graduate School in Partial Fulfillment of the Requirements for the Award of the Degree of Master of Science in Agricultural Education of Egerton University
Keywords: boys’ school dropout; education; Khat production; Khat consumption